National stakeholders’ workshop of the Ghana national science-policy dialogue platform on climate change, agriculture and food security: Review of activities and operations - Karbo, Naaminong; Botchway, Vincent Ansah; Sam, Kingsley Odum (2019)
A one-day workshop in Tamale, Ghana was organized to discuss opportunities to leverage partnership between the CCAFS West Africa’s policy-focused project and the Ghana national science-policy dialogue platform on climate-smart agriculture. Specifically, the meeting aimed to share experiences and achievements from the national and district levels science-policy dialogue platforms since their establishment and to dialogue about the way forward as well as plan and develop actions in accordance with CCAFS West Africa’s policy project that began in 2019.